2021
DOI: 10.5194/isprs-archives-xliii-b3-2021-469-2021
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Evolution of Ice Aprons in a Changing Climate in the Mont-Blanc Massif (Western European Alps)

Abstract: Abstract. Ice Apron (IA) is a poorly studied ice feature, commonly existing in all the world’s major mountain regions. This study aims to map the locations of the IAs in the Mont Blanc massif (MBM), making use of the very high-resolution optical satellite images from 2001, 2012 and 2019. 423 IAs were identified and accurately delineated in the MBM on the images from 2019, and their topographic characteristics were studied. We generated our own Digital Elevation Model (DEM) at 4 m resolution since the freely av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Thus, it is likely that underlying permafrost conditions aid the sustainability of IAs in the long term, and an increase in rock surface temperatures around IAs could result in IAs losing mass more rapidly. Kaushik et al (2021) further showed that most IAs exist in extremely rugged terrains: 51 % of the total IAs mapped exist in the TRI's high and very high ruggedness class, while only 8 % exist in the low ruggedness. Thus, comparing the terrain ruggedness to the area loss of IAs makes sense since the topography around the snow/ice bodies can critically influence their stability (Deline et al, 2015).…”
Section: Area Loss Of Ice Aprons and The Role Of Topographic Parametersmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, it is likely that underlying permafrost conditions aid the sustainability of IAs in the long term, and an increase in rock surface temperatures around IAs could result in IAs losing mass more rapidly. Kaushik et al (2021) further showed that most IAs exist in extremely rugged terrains: 51 % of the total IAs mapped exist in the TRI's high and very high ruggedness class, while only 8 % exist in the low ruggedness. Thus, comparing the terrain ruggedness to the area loss of IAs makes sense since the topography around the snow/ice bodies can critically influence their stability (Deline et al, 2015).…”
Section: Area Loss Of Ice Aprons and The Role Of Topographic Parametersmentioning
confidence: 96%
“…A precisely co-registered, high- resolution, robust 4 m DEM was obtained at the end of the processing steps. More detailed information about the processing parameters for DEM generation and co-registration can be found in Kaushik et al (2021). We used this DEM to compute topographic parameters like slope, aspect, curvature, elevation, TRI, mean annual rock surface temperature (MARST) and direct solar radiation.…”
Section: Digital Elevation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…IAs are very small ice bodies located on very steep slopes. The slant range acquisition geometry of SAR images is always associated with geometric distortions, which can create geometrical artefacts (GA): strong foreshortening, layover (active and passive) and shadow (active and passive) (Kaushik et al, 2021a). To study the temporal evolution of backscattering response from IAs, it is necessary to find areas free from these artefacts.…”
Section: Visibility Analysis For Identifying Ias Free From Geometric ...mentioning
confidence: 99%